Molecular Epidemiology of Human Papillomavirus Infection Among Chinese Women With Cervical Cytological Abnormalities - Wong, Eliza Lai-Yi; Cheung, Annie Wai-Ling; Chen, Zigui; Wong, Amy Yuen-Kwan; Yeung, Apple Chung-Man; Yau, Peter Sen-Yung; Chan, Paul Kay-Sheung (Frontiers in Public Health, 2022)
Background: Virtually all invasive cervical cancers are caused by persistent genital Human Papillomavirus (HPV) infection. Therefore, HPV-based screening becomes an essential tool as one of the cervical prevention strategies to reduce the disease burden. Population-specific epidemiologic information on HPV infection among women with cytological abnormalities is essential to inform the strategy of HPV-based screening programme. The study also explored the presence of cutaneous HPV types (Beta-β and Gamma-γ) in cervical infections. Method: A cross-sectional study on Chinese women aged ≥25 years who were referred to public specialist out-patient clinics for colposcopy or further management of cervical cytological abnormalities, were recruited between 2015 and 2016 in Hong Kong. HPV was detected and typified by the novel PCR-based Next-Generation Sequencing (NGS) strategies. Results: The overall HPV infection rate was 74% and detected in 222 of the 300 respondents, with the prevalence of cutaneous HPV infection being 2.3%. The overall prevalence of HPV infection among women with current cytological abnormalities was 79.1% (197/249). The age-specific prevalence of HPV (any-type HPV infection) among women with cytological abnormalities reached the first peak with 87.9% at the age group of 35-39 years and gradually declined to 56.0% at 55-59 years. While a second peak occurred at 65 years or above (92.9%). HPV58 (13.7%), HPV52 (11.7%), HPV53 (11.2%), HPV16 (10.0%), HPV18 (5.2%) and HPV51 (5.2%) were the top five high-risk HPV genotypes among women with cytological abnormalities. Any-HPV type infection was significantly associated with an abnormal cervical smear (OR = 3.7; 95% CI 2.0-7.1), and high-risk HPV infection was also significantly associated with an abnormal cervical smear (OR = 6.3; 95% CI 3.0-13.5). Conclusion: New evidence on the second peak of HPV infection at ≥65 years old suggests the necessity to review the current guideline for the cervical screening program extending to age 65 and above. Moreover, high prevalence of two HPV genotypes – high-risk HPV51 and potential high-risk HPV53, among women with cytological abnormalities – suggest further research work is needed to confirm the contributory role of HPV51 and HPV53 in cervical cancer and the needs of inclusion in the next generation of HPV vaccine.